A light on the hill [large type] - Cossette, Connilyn (Cossette, Connilyn. Cities of refuge., 2018)
Seven years ago, Moriyah was taken captive in Jericho and branded with the mark of the Canaanite gods. Now the Israelites are experiencing peace in their new land, by Moriyah has yet to find her own peace. Because of the shameful mark on her face, she hides behind her veil at all times and suffers the disdain of the townspeople. The her father finds someone to marry her--but things go horribly wrong. Moriyah is forced to flee to one of the newly established Levitical cities of refuge, wildly unprepared for the dangers she will face.